An automated and multiparametric algorithm for objective analysis of meibography images - Xiao, Peng; Luo, Zhongzhou; Deng, Yuqing; Wang, Gengyuan; Yuan, Jin (Quantitative imaging in medicine and surgery, 2021)
Meibography is a non-contact imaging technique used by ophthalmologists and eye care practitioners to acquire information on the characteristics of meibomian glands. One of its most important applications is to assist in the evaluation and diagnosis of meibomian gland dysfunction (MGD). As the artificial qualitative analysis of meibography images can lead to low repeatability and efficiency, automated and quantitative evaluation would greatly benefit the image analysis process. Moreover, since the morphology and function of meibomian glands varies at different stages of MGD, multiparametric analysis offering more comprehensive information could help in discovering subtle changes to glands during MGD progression. Therefore, an automated and multiparametric objective analysis of meibography images is urgently needed. An algorithm was developed to perform multiparametric analysis of meibography images with fully automatic and repeatable segmentation based on image contrast enhancement and noise reduction. The full architecture can be divided into three steps: (I) segmentation of the tarsal conjunctiva area as the region of interest (ROI); (II) segmentation and identification of glands within the ROI; and (III) quantitative multiparametric analysis including a newly defined gland diameter deformation index ( ), gland tortuosity index ( ), and gland signal index ( ). To evaluate the performance of this automated algorithm, the similarity index ( ) and the segmentation error including the false-positive rate ( ) and the false-negative rate ( ) were calculated between the manually defined ground truth and the automatic segmentations of both the ROI and meibomian glands of 15 typical meibography images. The results of the performance evaluation between the manually defined ground truth and automatic segmentations were as follows: for ROI segmentation, the similarity index ( )=0.94±0.02, the false-positive rate ( )=6.02%±2.41%, and the false-negative rate ( )=6.43%±1.98%; for meibomian gland segmentation, the similarity index ( )=0.87±0.01, the false-positive rate ( )=4.35%±1.50%, and the-false negative rate ( )=18.61%±1.54%. The algorithm was successfully applied to process typical meibography images acquired from subjects of different meibomian gland health statuses, by providing the gland area ratio ( ), the gland length ( ), gland width ( ), gland diameter deformation index ( ), gland tortuosity index ( ), and gland signal index ( ). A fully automated algorithm was developed which demonstrated high similarity with moderate segmentation errors for meibography image segmentation compared with the manual approach, offering multiple parameters to quantify the morphology and function of meibomian glands for the objective evaluation of meibography images.